(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
Carcinogenesis, oncogenesis or tumourigenesis is a complex biomolecular mechanism that could progressively transform normal cells to malignant forms. Proper diet constituting natural fruits and vegetables enriched in bioactive components can reduce the risk factors of several forms of human cancer and other critical ailments. Endemic and endangered Cucurbitaceous climber of Darjeeling hills, Herpetospermum darjeelingense (C.B. Clarke) H. Schaef. & S.S. Renner [Edgaria darjeelingensis C.B. Clarke] is a repository of bioactive anti-cancer metabolites as depicted by the presence of fourteen anti-carcinogenic molecules explored via GC-MS analysis, which could potentially minimize the threats of various forms of cancer. The anti-cancer compounds cover about 79.22% of total GC-MS area percentage out of the total thirty four compounds detected. The explored cellular biosynthesis pathway of these anti-carcinogenic metabolites seems to follow a systemic metabologenesis pattern that may be required for the day-to-day survival of the plant and not a mere chance factor, which could have stressed the plant to produce those biochemical molecules. Isolation, pharmaceutical screening of these compounds and their medical application can revolutionise the dimension of the global cancer research in the near future.